Evolution of the Corporation in the United States: Stabilized Scarcity and Vested Interests. Issue 1 (2nd January 2019) - Atkinson, Glen; Hake, Eric R.; Paschall, Stephen P.
Abstract: The widening of markets beginning in the late nineteenth century in the United States involved changes in the financial and legal institutions supporting production for large-scale markets. The evolution of the corporation under these circumstances reflects the role of the legal system in formulation of formal rules which favor vested interests. As Thorstein Veblen said, "A constitutional government is a business government." This article examines the co-evolution of the legal system and the economic system as they relate to the merger movement at the turn of the twentieth century, the increased use of the corporate form, and the emphasis on pecuniary values over production to secure stabilized scarcity in the midst of cutthroat competition and deflation. The resultant financialization of the economy which continues today was reinforced by such legal rules as the Fourteenth Amendment's protection of property, including intangible property, and the Rule of Reason accommodating some instances of monopolization. These stabilization policies have secured the rentiers' return at the cost of the long term health of the national economy. John R. Commons' observations on artificial selection and the use of law to make capitalism better offer a solution through laws regulating the detrimental aspects of financialization.